2018
DOI: 10.1155/2018/9240206
|View full text |Cite
|
Sign up to set email alerts
|

Variable Pore Structure and Gas Permeability of Coal Cores after Microwave Irradiation

Abstract: The experimental work in this paper investigated the effect of microwave energy on pore structure and gas permeability of coal cores. Fifteen coal samples were irradiated under the condition of 2.45 GHz with 6 kW. The effect of microwave irradiation on the pore structure of coal samples was evaluated by nuclear magnetic resonance (NMR). The water saturation degree has little influence on transverse relaxation time (T2) distribution before the microwave treatment. By contrast, water saturation degree obviously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…However, in the literature, there is no clear explanation or evidence on the effect of microwave irradiation time on the porosity of the solid samples. Our results are compatible with the previous work of Hong et al…”
Section: Results and Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, in the literature, there is no clear explanation or evidence on the effect of microwave irradiation time on the porosity of the solid samples. Our results are compatible with the previous work of Hong et al…”
Section: Results and Discussionsupporting
confidence: 94%
“…However, in the literature, there is no clear explanation or evidence on the effect of microwave irradiation time on the porosity of the solid samples. Our results are compatible with the previous work of Hong et al 32 The pore size distribution is plotted in Figure 6, which is set by applying the methodology of Barrett−Joyner−Halenda (BJH). The calculated specific surface area, porosity (P), total pore volume (V p ), and maximum pore volume (P max ) for all the samples are given in Table 2.…”
Section: α ν νsupporting
confidence: 92%
See 1 more Smart Citation
“…Jones reported that in response to different boundary volumes of particles to microwave energy, the ability of small particles to absorb microwaves is lower when the power density is constant. Hong , showed that the porosity of coal samples increased clearly after microwave heating. Moreover, the fractal dimensions of coal and rock decreased after the microwave energy treatment.…”
Section: Introductionmentioning
confidence: 99%